2016
DOI: 10.1007/s11144-016-1039-0
|View full text |Cite
|
Sign up to set email alerts
|

The removal of chlorophenols from aqueous solutions using activated carbon adsorption integrated with H2O2 oxidation

Abstract: The removal of eight chlorophenols (2-CP, 3-CP, 4-CP, 2,3-DCP, 2,4-DCP, 2,5-DCP, 2,6-DCP and 2,4,6-TCP) using adsorption on activated carbon and adsorption in the presence of hydrogen peroxide was investigated. The influence of the pH, activated carbon dosage and hydrogen peroxide concentration were studied. The effects of the chlorine atom position and the chlorine content in the chlorophenol molecules on their degradation were also studied. The results revealed that the integration of the activated carbon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 41 publications
3
11
0
1
Order By: Relevance
“…This suggests that the adsorption of phenols on the ATPCs and CB-V follows the pseudo-second-order kinetic model and chemical adsorption might be the rate-limiting step involving valency forces through sharing or exchange of electrons between adsorbent surface and adsorbate molecules [20]. The similar phe- nomena in the adsorption of phenolic compounds have also been observed by other authors [21][22][23][24][25][26][27]. All of the adsorbates were adsorbed faster on CB-V carbon black than on ATPCs.…”
Section: Adsorption Kineticssupporting
confidence: 79%
See 2 more Smart Citations
“…This suggests that the adsorption of phenols on the ATPCs and CB-V follows the pseudo-second-order kinetic model and chemical adsorption might be the rate-limiting step involving valency forces through sharing or exchange of electrons between adsorbent surface and adsorbate molecules [20]. The similar phe- nomena in the adsorption of phenolic compounds have also been observed by other authors [21][22][23][24][25][26][27]. All of the adsorbates were adsorbed faster on CB-V carbon black than on ATPCs.…”
Section: Adsorption Kineticssupporting
confidence: 79%
“…Rincon-Silva et al [23] as well as Strachowski and Bystrzejewski [24] found that 4CP was adsorbed faster than Ph onto lignocellulose-derived activated carbon and carbon nanotubes, respectively. Garba and Rahim [25] reported that DCP was adsorbed faster than 4CP on the activated carbon prepared from an agricultural waste, while Kuśmierek [27] observed the same regularity on the Ceca L2S-powdered activated carbon. Fig.…”
Section: Adsorption Kineticsmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, AC is able to activate hydrogen peroxide, producing reactive free radicals as the oxidizing agents of organic pollutants: AC+H2O2AC++OH+OH AC+H2O2AC++OH2+H+ …”
Section: Introductionmentioning
confidence: 99%
“…They can find their way to the environment since they were detected at high concentrations in wastewater treatment plant (WWTP) and discharged effluents close to industrial activities 3 . Due to the toxicity and carcinogenic properties, the long term exposure to chlorophenols at high concentration levels was found to cause liver, kidney and neurological defects, and therefore, their removal from water sources becomes environmentally warranted 4,5 . There are different physical and chemical technologies currently used for removal phenol and its derivative compounds from their aqueous solution like oxidation 6 , adsorption 7 and ion exchange 8 .…”
Section: Introductionmentioning
confidence: 99%